Research and teaching PA: Towards research as teaching. (March 2016) - van der Meer, Frans-Bauke; Marks, Peter
Research and teaching are core business of academic institutions. The research context is thought to be fruitful for teaching and learning, and students may contribute to research. But how exactly does the interplay between research and teaching take place and how, in what respects and under which conditions, does this contribute to the quality of research and teaching? The article makes an inventory of functions of research in teaching in public administration curricula. It elaborates on conditions and mechanisms for effective realization of these functions, based on the contributions to this special issue, literature and our own insights and experiences. We evaluate and reflect on different functions and modes of linking research and teaching and to explore relevant conditions for their use.